A managerial perspective of how resource-based view theory leads to competitive advantage - Geraldes, Rita Isabel Alves (2019)
A clear business strategy is often emphasized by managers as vital to achieve a sustainable performance. However, when asked concerning its strategy in place, many of them cannot provide an answer. (Collis and Rukstad, 2008) Many researchers defend that considering the turbulence of today’s business environment, the resource-based view is the most suitable theoretical starting point in a strategic analysis (Guo, 2007). The aim of this project is to understand how the theoretical frameworks analyzed can be combined in order to understand from a resource-based view standpoint to what the degree the theory can be improved and to assess the proper understanding between the organizational structure and strategy, performance and resources/capabilities. This research is intended to contribute to a better understanding of the theory so as to help firms to achieve a competitive edge since these results aim to be essential, particularly to researchers and scholars, as a source of reference material for further research. To do so, it was adopted a qualitative research that comprised the collection of data through interviews a key individual (professors and experts on the topic) in order to reach a better understanding of the topic. Using also secondary data, the researcher intends to develop a conceptual/extended framework of the VRIO-Framework current in place. In accordance with above research purpose following conclusions have been obtained: (1) the comparison between relevant strategic management theories and tools that are attributed as key factors to surmise a sustainable competitive advantage; (2) the actual status of resource-based view theory as a starting point in strategic analysis, it main criticisms and it relation with dynamic capabilities; (3) the impact of managerial organizational characteristics, individual dynamics and organizational values as factors that influence the mode of strategy.